Composite diaphragm, preparation method thereof and battery

By applying a composite coating of sodium superion conductor type phosphate and single-arm carbon nanotubes on the surface of the polyolefin separator, the problems of easy shrinkage of the polyolefin separator at high temperatures and poor electrolyte wetting are solved, which significantly improves the heat resistance of the separator and the cycling performance of the battery.

CN119601902APending Publication Date: 2025-03-11GUANGZHOU GREATER BAY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411728938.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing polyolefin separators are prone to shrink at high temperatures, with low mechanical strength and puncture strength, resulting in short circuits of the battery and poor wetting in the electrolyte, affecting ionic conductivity and cycling performance.

Method used

Using a composite diaphragm containing sodium superion conductor type phosphate, single-arm carbon nanotubes and binder, the heat shrinkage resistance of the diaphragm, the infiltration performance and liquid absorption capacity of the electrolyte, as well as ionic conductivity and puncture strength are improved through the design of the coating.

Benefits of technology

The excellent heat shrinkage resistance of the composite separator, the good wetting performance of the electrolyte and the high puncture strength are achieved, and the capacity and circulation performance of the battery containing the separator are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601902A_ABST
    Figure CN119601902A_ABST
Patent Text Reader

Abstract

The invention relates to a composite diaphragm, a preparation method thereof and a battery, and belongs to the technical field of battery materials, the composite diaphragm comprises a base membrane and a coating distributed on the surface of the base membrane; the coating comprises sodium super-ionic conductor type phosphate, a single-arm carbon nano tube and a binding agent, the mass ratio of the sodium super-ion conductor type phosphate to the single-arm carbon nanotube is (20-80): 1. The composite diaphragm provided by the invention has excellent heat shrinkage resistance, electrolyte infiltration performance and liquid absorption capability, and relatively high ionic conductivity and puncture strength, and the battery comprising the composite diaphragm has relatively high capacity and excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a composite diaphragm and a preparation method thereof, and a battery. Background Art

[0002] As an important component of the battery, the diaphragm has the function of separating the positive and negative electrodes to avoid short circuits and providing a channel for the transmission of sodium ions. Currently, commercial diaphragms are mainly composed of polyolefin materials (including PP, PE and PP / PE composites). However, polyolefin materials have relatively poor thermal stability and are prone to shrinkage when the battery operating temperature is high, which can easily cause battery short circuits; polyolefin diaphragms have low mechanical strength and puncture strength, and are easily punctured, causing battery short circuits. In addition, polyolefin diaphragms have poor wettability in the electrolyte, which will affect the ionic conductivity and thus the cycle performance of the battery. Summary of the invention

[0003] In response to one or more technical problems existing in the prior art, the present invention provides a composite diaphragm, a preparation method thereof, and a battery. The composite diaphragm provided by the present invention has excellent heat shrinkage resistance, electrolyte wetting performance and liquid absorption capacity, as well as high ionic conductivity and puncture strength. The battery containing the composite diaphragm has high capacity and excellent cycle performance.

[0004] In a first aspect, the present invention provides a composite diaphragm, which comprises a base membrane and a coating distributed on the surface of the base membrane; the coating comprises sodium superion conductor phosphate, single-arm carbon nanotubes and a binder; the mass ratio of the sodium superion conductor phosphate to the single-arm carbon nanotubes is 20 to 80:1.

[0005] Preferably, the particle size of the sodium superion conductor phosphate is 100 to 300 nm; and / or

[0006] The total mass of the sodium superion conductor phosphate and the single-arm carbon nanotube is 5 to 20 times the mass of the binder.

[0007] Preferably, the sodium superion conductor phosphate is one or more of sodium vanadium phosphate, sodium vanadium iron phosphate, and sodium vanadium manganese phosphate.

[0008] Preferably, the base film is a polyolefin base film, preferably one of a PE base film, a PP base film, and a PP / PE composite base film; and / or

[0009] The binder is PVDF 。

[0010] Preferably, the base film has a thickness of 5 to 20 μm; and / or

[0011] The porosity of the base film is 30-60%.

[0012] Preferably, the coating has a thickness of 2 to 5 μm.

[0013] In a second aspect, the present invention provides a method for preparing the composite diaphragm according to the first aspect, the preparation method comprising:

[0014] S1. mixing a sodium superionic conductor type phosphate, a single-arm carbon nanotube, a binder and an organic solvent to obtain a coating slurry;

[0015] S2. Distribute the coating slurry on the base film, remove the solvent, and obtain a composite diaphragm.

[0016] Preferably, the solid content of the coating slurry is 10-40%.

[0017] Preferably, the organic solvent is one or more of N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, triethyl phosphate, and N,N-dimethylformamide.

[0018] The present invention provides a battery in a third aspect, comprising the composite diaphragm described in the first aspect or the composite diaphragm prepared by the preparation method described in the second aspect.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects:

[0020] The surface of the composite diaphragm provided by the present invention has a coating comprising a sodium superionic conductor phosphate material with a small particle size and a single-arm carbon nanotube. The sodium superionic conductor phosphate material has a stable crystal structure, good thermal stability and a low expansion coefficient, which can improve the heat resistance of the composite diaphragm; the sodium superionic conductor phosphate material has a three-dimensional ion transmission channel, has higher ion and electron transmission characteristics and better sodium storage performance, which can effectively improve the sodium ion migration rate of the composite diaphragm; at the same time, the sodium superionic conductor phosphate material with a small particle size has a higher packing density, has a supporting effect on the base film, and can further improve the heat shrinkage resistance of the diaphragm. Single-walled carbon nanotubes have the characteristics of high conductivity, high specific surface area and high flexibility, which can not only effectively improve the conductivity of the composite diaphragm, improve the conductivity of the positive electrode side diaphragm, reduce the interface impedance, but also improve the electrolyte wettability, liquid absorption capacity and puncture strength of the diaphragm. In addition, the sodium superionic conductor phosphate material and the single-walled carbon nanotubes synergistically improve the ionic conductivity of the diaphragm and the cycle performance of the battery containing the diaphragm.

[0021] The composite diaphragm provided by the present invention has excellent heat shrinkage resistance, electrolyte wetting performance and liquid absorption capacity, as well as high ion conductivity and puncture strength. The battery containing the composite diaphragm has high capacity and excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 It is a schematic diagram of the structure of the composite diaphragm provided by the present invention;

[0024] Figure 2 It is a cycle performance diagram of batteries assembled with the composite diaphragms provided in Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] In a first aspect, the present invention provides a composite diaphragm, which comprises a base membrane and a coating distributed on the surface of the base membrane; the coating comprises sodium superion conductor phosphate, single-arm carbon nanotubes and a binder; the mass ratio of the sodium superion conductor phosphate to the single-arm carbon nanotubes is 20 to 80:1.

[0027] The surface of the composite diaphragm provided by the present invention has a coating comprising a sodium superionic conductor type phosphate material with a small particle size and a single-arm carbon nanotube. The sodium superionic conductor type phosphate material has a stable crystal structure, good thermal stability and a low expansion coefficient, which can improve the heat resistance of the composite diaphragm; the sodium superionic conductor type phosphate material has a three-dimensional ion transmission channel, has higher ion and electron transmission characteristics and better sodium storage performance, and can effectively improve the sodium ion migration rate of the composite diaphragm. At the same time, the sodium superionic conductor type phosphate material with a small particle size has a higher packing density, has a supporting effect on the base film, and can further improve the heat shrinkage resistance of the diaphragm. Single-walled carbon nanotubes have the characteristics of high conductivity, high specific surface area and high flexibility, which can not only effectively improve the conductivity of the composite diaphragm, improve the conductivity of the positive electrode side diaphragm, reduce the interface impedance, but also improve the electrolyte wettability, liquid absorption capacity and puncture strength of the diaphragm. In addition, the sodium superionic conductor type phosphate material and the single-walled carbon nanotubes synergistically improve the ionic conductivity of the diaphragm and the cycle performance of the battery containing the diaphragm.

[0028] The composite diaphragm provided by the present invention has excellent heat shrinkage resistance, electrolyte wetting performance and liquid absorption capacity, as well as high ion conductivity and puncture strength. The battery containing the composite diaphragm has high capacity and excellent cycle performance.

[0029] The present invention controls the mass ratio of sodium superionic conductor phosphate to single-arm carbon nanotubes within the above range to obtain a diaphragm with excellent performance; the inventors found that, under the condition that other conditions remain unchanged, if the amount of sodium superionic conductor phosphate is too small, the improvement of the heat shrinkage resistance of the diaphragm is not obvious, and it is impossible to effectively construct a three-dimensional ion transmission channel in the diaphragm and improve the sodium storage performance. The heat shrinkage performance, ion conductivity, capacity and cycle performance of the diaphragm obtained after coating are all deteriorated. If the amount of sodium superionic conductor phosphate is too large, the conductivity of the diaphragm is poor, the ion conductivity is reduced, the wettability and liquid absorption capacity are deteriorated, and finally the cycle performance of the battery containing the diaphragm is deteriorated.

[0030] The present invention adopts sodium superionic conductor phosphate with small particle size to ensure that the obtained diaphragm has excellent heat shrinkage resistance and high ionic conductivity, and the assembled battery has high battery capacity and excellent cycle performance; the inventors found that if the particle size of the sodium superionic conductor phosphate is too large, the thermal shrinkage rate of the diaphragm will increase and the ionic conductivity will decrease, which will further cause the battery capacity and cycle performance of the assembled battery to deteriorate.

[0031] According to some preferred embodiments, the particle size of the sodium superion conductor phosphate is 100 to 300 nm.

[0032] According to some preferred embodiments, the total mass of the sodium superion conductor phosphate and the single-arm carbon nanotube is 5 to 20 times the mass of the binder (for example, it can be 5 times, 6 times, 8 times, 10 times, 12 times, 15 times, 16 times, 18 times or 20 times). The present invention controls the amount of binder within the above range to ensure the bonding strength between the coating and the base film without affecting the performance of the diaphragm. The inventors found that if the amount of binder is too large, pore blockage is likely to occur, affecting the air permeability of the diaphragm and affecting the performance of the diaphragm; if the amount of binder is too small, the coating is not firmly bonded and is prone to powdering, affecting the heat resistance and liquid absorption performance of the diaphragm, and thus affecting the cycle performance of the battery.

[0033] According to some preferred embodiments, the sodium superion conductor phosphate is one or more of sodium vanadium phosphate, sodium vanadium iron phosphate, and sodium vanadium manganese phosphate.

[0034] According to some preferred embodiments, the base film is a polyolefin base film, preferably one of a PE base film, a PP base film, and a PP / PE composite base film.

[0035] According to some preferred embodiments, the binder is PVDF 。

[0036] According to some preferred embodiments, the base film has a thickness of 5 to 20 μm (eg, 5 μm, 10 μm, 15 μm or 20 μm).

[0037] According to some preferred embodiments, the porosity of the base film is 30-60% (for example, 30%, 35%, 40%, 45%, 50%, 55% or 60%).

[0038] According to some preferred embodiments, the coating has a thickness of 2 to 5 μm (eg, 2 μm, 3 μm, 4 μm or 5 μm).

[0039] It should be noted that the present invention does not specifically limit the type, thickness, porosity of the base film and the thickness of the coating. The present invention limits the type, thickness, porosity of the base film and the thickness of the coating to the above range only to illustrate the technical solution of the present invention, but not to limit it. It can be selected and adjusted according to actual use requirements.

[0040] In a second aspect, the present invention provides a method for preparing the composite diaphragm according to the first aspect, the preparation method comprising:

[0041] S1. mixing a sodium superionic conductor type phosphate, a single-arm carbon nanotube, a binder and an organic solvent to obtain a coating slurry;

[0042] S2. Distribute the coating slurry on the base film, remove the solvent, and obtain a composite diaphragm.

[0043] According to some preferred embodiments, the solid content of the coating slurry is 10-40% (for example, it may be 10%, 15%, 20%, 25%, 30%, 35% or 40%).

[0044] According to some preferred embodiments, the organic solvent is one or more of N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, triethyl phosphate, and N,N-dimethylformamide.

[0045] The present invention provides a battery in a third aspect, comprising the composite diaphragm described in the first aspect or the composite diaphragm prepared by the preparation method described in the second aspect.

[0046] The battery assembled by the present invention using a composite diaphragm with excellent heat shrinkage resistance, electrolyte wetting performance and liquid absorption capacity, as well as high ion conductivity and puncture strength has high capacity and excellent cycle performance.

[0047] In order to more clearly illustrate the technical scheme and advantages of the present invention, the present invention is further described below in conjunction with the examples. It should be noted that, in order to better illustrate the technical scheme, the following examples and comparative examples of the present invention use PE film as the base film, and the scheme of the present invention is also applicable to other base films. The present invention does not specifically limit the source of each reagent used in the examples and comparative examples, and can be directly purchased or synthesized by itself. The nano sodium vanadium phosphate of the present invention can be directly purchased or prepared by itself, wherein the method for preparing nano sodium vanadium phosphate by itself comprises: dissolving 3.2g of vanadium oxysulfate in 100mL of deionized water; then adding sodium hydroxide solution (obtained by dissolving 6g of sodium hydroxide in 100mL of deionized water) thereto, stirring and filtering to obtain vanadium hydroxide; dissolving 2.4g of sodium fluoride and 18g of sodium dihydrogen phosphate in deionized water; adding vanadium hydroxide thereto, stirring, filtering and drying to obtain sodium vanadium phosphate with a particle size of about 150nm.

[0048] Example 1

[0049] 3 g of sodium vanadium phosphate (with a particle size of 150 nm), 0.1 g of single-arm carbon nanotubes, 0.3 g of PVDF and 15 g of N,N-dimethylacetamide were mixed and stirred to obtain a coating slurry;

[0050] The coating slurry was coated on a PE-based membrane (porosity of 48%) with a thickness of 9 μm, with a coating thickness of 3 μm, to obtain a composite separator.

[0051] Example 2

[0052] 2 g of sodium vanadium phosphate (with a particle size of 100 nm), 0.1 g of single-arm carbon nanotubes, 0.21 g of PVDF and 10 g of dimethyl sulfoxide were mixed and stirred to obtain a coating slurry;

[0053] The coating slurry was coated on a PE-based membrane (porosity of 48%) with a thickness of 9 μm, with a coating thickness of 3 μm, to obtain a composite separator.

[0054] Example 3

[0055] 8 g of sodium vanadium phosphate (with a particle size of 300 nm), 0.1 g of single-arm carbon nanotubes, 0.81 g of PVDF and 15 g of N-methylpyrrolidone were mixed and stirred to obtain a coating slurry;

[0056] The coating slurry was coated on a PE-based membrane (porosity of 48%) with a thickness of 9 μm, with a coating thickness of 3 μm, to obtain a composite separator.

[0057] Example 4

[0058] 3 g of sodium vanadium iron phosphate (particle size of 150 nm), 0.1 g of single-arm carbon nanotubes, 0.62 g of PVDF and 32 g of triethyl phosphate were mixed and stirred to obtain a coating slurry;

[0059] The coating slurry was coated on a PE-based membrane (porosity of 48%) with a thickness of 9 μm, with a coating thickness of 3 μm, to obtain a composite separator.

[0060] Example 5

[0061] 3 g of sodium manganese vanadium phosphate (with a particle size of 150 nm), 0.1 g of single-arm carbon nanotubes, 0.16 g of PVDF and 15 g of N,N-dimethylformamide were mixed and stirred to obtain a coating slurry;

[0062] The coating slurry was coated on a PE-based membrane (porosity of 48%) with a thickness of 9 μm, with a coating thickness of 3 μm, to obtain a composite separator.

[0063] Comparative Example 1

[0064] It is basically the same as Example 1, except that the particle size of sodium vanadium phosphate is 1 μm.

[0065] Comparative Example 2

[0066] It is basically the same as Example 1, except that no single-arm carbon nanotubes are added.

[0067] Comparative Example 3

[0068] The method is basically the same as Example 1, except that no sodium vanadium phosphate is added.

[0069] Comparative Example 4

[0070] It is basically the same as Example 1, except that multi-arm carbon nanotubes are used instead of single-arm carbon nanotubes.

[0071] Comparative Example 5

[0072] The method is basically the same as Example 1, except that the amount of sodium vanadium phosphate used is 1 g.

[0073] Comparative Example 6

[0074] The method is basically the same as Example 1, except that the amount of sodium vanadium phosphate used is 10 g.

[0075] Comparative Example 7

[0076] 10g Al2O3 and 0.1g dispersant (ammonium polyacrylate) were weighed and dispersed in 100mL water, and then 2g binder (polyacrylate), 1.8g carboxymethyl cellulose (CMC) solution, and 0.02g wetting agent (nonylphenol polyoxyethylene ether) were added and stirred to obtain slurry. The slurry was coated on a 9μm PE base film using a micro-gravure plate with a coating thickness of 3μm.

[0077] Comparative Example 8

[0078] The separator only uses a PE-based film, specifically a PE-based film with a thickness of 9 μm and a porosity of 48%.

[0079] The performance of the composite diaphragm and the battery containing the composite diaphragm provided in the embodiments and comparative examples of the present invention was tested, and the specific testing method is as follows:

[0080] Composite diaphragm performance

[0081] Air permeability: A Guellini permeameter is used to measure the time required for 100 mL of gas to pass through a 1 square inch membrane under a pressure of 1.21 KPa.

[0082] Liquid absorption rate: tested in accordance with national standard QB / T 4173-2011.

[0083] Puncture strength: tested according to national standard GB / T 23318-2009.

[0084] Heat shrinkage performance: Two pieces of A4 paper sandwich a 10cm*10cm composite diaphragm and then place it on a stainless steel plate and heat it in a 130℃ oven for 1h. After heating, measure the longitudinal and transverse marked lengths again and calculate the shrinkage rate.

[0085] Ionic conductivity: In a glove box, assemble the diaphragm into a button cell, add an appropriate amount of electrolyte, and test the AC impedance to obtain; σ = L / (Rb*A), where σ is the ionic conductivity (S·cm -1 ), L is the thickness of the diaphragm (cm); Rb is the intrinsic resistance of the diaphragm (Ω); A is the effective area (cm 2 ).

[0086] Initial capacity and capacity retention rate test: The separator provided by the embodiment of the present invention and the comparative example is assembled into a button cell with a positive electrode sheet and a negative electrode sheet, wherein the mass ratio of the positive electrode active material, the binder and the conductive agent in the positive electrode sheet is 94:3:3, the positive electrode active material is sodium vanadium phosphate, the binder is PVDF, and the conductive agent is conductive carbon black (SP); the negative electrode is a metal sodium sheet; the electrolyte is a NaClO4 solution with a concentration of 1 mol / L, wherein the solvent is a mixture of ethylene carbonate (EC) and propylene carbonate (PC) in a volume ratio of 1:1. The battery is in the voltage range of 2 to 4.0 V, after 0.1C activation, the 1C rate discharge capacity is tested as the initial capacity, and the capacity retention rate of the battery after 300 cycles at a 1C rate is tested.

[0087] Table 1. Performance data of composite diaphragms prepared in various embodiments and comparative examples of the present invention and batteries containing the composite diaphragms

[0088]

[0089] As shown in Table 1, the composite membrane provided by the present invention has excellent heat shrinkage resistance (130°C, the transverse and longitudinal shrinkage rates are both less than 2%), electrolyte wetting performance and liquid absorption capacity (liquid absorption rate greater than 160%), and high ionic conductivity (not less than 0.7S cm -1 ) and puncture strength (greater than 4.8gf), the battery containing the composite separator has a high capacity (higher than 120mAh) and excellent cycle performance (the capacity retention rate of the battery cell after 300 cycles at 1C rate is not less than 88%).

[0090] Compared with Example 1, Comparative Example 1 uses large-particle sodium superion conductor phosphate, which has a small packing density and an insignificant supporting effect on the base membrane. The heat shrinkage resistance of the diaphragm obtained after coating is reduced. At the same time, the large-particle sodium superion conductor phosphate has a poorer ion conduction effect than the small-particle sodium superion conductor phosphate. The ionic conductivity of the obtained diaphragm is reduced, thereby affecting the cycle performance of the battery containing the diaphragm.

[0091] Compared with Example 1, Comparative Example 2 did not add single-walled carbon nanotubes with high conductivity and flexibility, resulting in reduced ion conductivity and puncture strength of the composite diaphragm; at the same time, the specific surface area of ​​the composite diaphragm was small, which led to reduced electrolyte wettability and liquid absorption capacity. Comparative Example 3 did not add sodium vanadium phosphate, and the heat shrinkage resistance and ion conductivity of the diaphragm obtained after coating were reduced, which led to reduced capacity and poor cycle performance of the battery containing the diaphragm. Figure 2It can be seen that the cycle performance of the battery assembled with the composite diaphragm provided in Example 1 of the present invention is significantly better than the cycle performance of the battery assembled with the composite diaphragms provided in Comparative Examples 2 and 3. It can be seen that the sodium superion conductor type phosphate material and the single-walled carbon nanotubes synergistically improve the ionic conductivity of the diaphragm and the cycle performance of the battery containing the diaphragm.

[0092] Compared with Example 1, Comparative Example 4 uses multi-arm carbon nanotubes instead of single-walled carbon nanotubes. Due to the low aspect ratio, small specific surface area and poor flexibility of multi-walled carbon nanotubes, the wettability and liquid absorption capacity of the diaphragm obtained after coating are deteriorated, and the puncture strength is reduced, which ultimately leads to the deterioration of the cycle performance of the battery containing the diaphragm.

[0093] Compared with Example 1, the amount of sodium superionic conductor phosphate used in Comparative Example 5 is too small, and the improvement of the heat shrinkage resistance of the diaphragm is not obvious. It is impossible to effectively construct a three-dimensional ion transmission channel in the diaphragm and improve the sodium storage performance. The heat shrinkage performance, ion conductivity, battery capacity and cycle performance of the diaphragm obtained after coating are all deteriorated. The amount of sodium superionic conductor phosphate used in Comparative Example 6 is too large, the conductivity of the diaphragm is poor, the ion conductivity is reduced, the wettability and liquid absorption capacity are all deteriorated, and ultimately the cycle performance of the battery containing the diaphragm is deteriorated.

[0094] Compared with Example 1, the heat shrinkage resistance, liquid absorption capacity, ionic conductivity, and puncture strength of the composite diaphragm containing the coating prepared in Comparative Example 7 are significantly reduced, and the capacity and cycle performance of the battery containing the diaphragm are significantly deteriorated. In addition, compared with Comparative Example 8 (PE-based film), although the coating in Comparative Example 7 significantly improves the heat shrinkage resistance of the composite diaphragm, it does not significantly improve the liquid absorption capacity, ionic conductivity, and puncture strength of the diaphragm, which leads to no significant improvement in the capacity and cycle performance of the battery containing the diaphragm.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite diaphragm, characterized in that: The composite diaphragm comprises a base film and a coating distributed on the surface of the base film; the coating comprises sodium superionic conductor phosphate, single-arm carbon nanotubes and a binder; the mass ratio of the sodium superionic conductor phosphate to the single-arm carbon nanotubes is 20 to 80:

1.

2. The composite diaphragm according to claim 1, characterized in that: The particle size of the sodium superion conductor phosphate is 100 to 300 nm; and / or The total mass of the sodium superion conductor phosphate and the single-arm carbon nanotube is 5 to 20 times the mass of the binder.

3. The composite diaphragm according to claim 1, characterized in that: The sodium superionic conductor phosphate is one or more of sodium vanadium phosphate, sodium vanadium iron phosphate, and sodium vanadium manganese phosphate.

4. The composite diaphragm according to claim 1, characterized in that: The base film is a polyolefin base film, preferably a PE base film, a PP base film, or a PP / PE composite base film; and / or The binder is PVDF 。 5. The composite diaphragm according to claim 1, characterized in that: The thickness of the base film is 5 to 20 μm; and / or The porosity of the base film is 30-60%.

6. The composite diaphragm according to claim 5, characterized in that: The coating has a thickness of 2 to 5 μm.

7. A method for preparing the composite diaphragm according to any one of claims 1 to 6, characterized in that: The preparation method comprises: S1. mixing a sodium superionic conductor type phosphate, a single-arm carbon nanotube, a binder and an organic solvent to obtain a coating slurry; S2. Distribute the coating slurry on the base film, remove the solvent, and obtain a composite diaphragm.

8. The preparation method according to claim 7, characterized in that: The solid content of the coating slurry is 10-40%.

9. The preparation method according to claim 7, characterized in that: The organic solvent is one or more of N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, triethyl phosphate, and N,N-dimethylformamide.

10. A battery, characterized in that: It includes the composite diaphragm described in any one of claims 1 to 6 or the composite diaphragm prepared by the preparation method described in any one of claims 7 to 9.